The Effectiveness of BSW (Building A Scholar Writing) on Writing Skill - Mohammad Arief Wahyudi (Penerbit STKIP PGRI Bangkalan, 2025)
The goal of this investigation is to determine if BSW is an effective model for writing skills. When it was necessary to explain the writing material to the students, the BSW (Building Scholar Writing) model was selected. Unlike qualitative studies in which BSW works as a theory, the study employed quantitative, experimental, pre- and post-test method, among others, using SPSS (statistical package for social sciences) for the analysis. The school used for the research was the Eighteen students from the Eleventh Grade IPA at MA AN- Namirah as the respondents. There was a test which formed part of the quantitative data collection and research, this was a one group Pre-test and Post-test experimental design. The participants were subjected to a test prior to being enrolled, and then again after completion of the course. In this situation, the focus is on analyzing the data from the pre-test and post-test videos. The mean score in the post test was significantly lower than that in the pretest. There was a noticeable increase in writing skills after practice using BSW technique, which the students adopted.